2017
DOI: 10.1111/auar.12172
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Investor Protection Pressures versus Firm Incentives in the Disclosure of Integrated Reporting

Abstract: Corporate disclosures aim to decrease the expectation gap between investors, decrease the advantage of informed investors and consequently reduce information asymmetry. However, the existence of higher numbers of companies' reports makes the decision making of firms' stakeholders difficult. To avoid these problems, companies have started to disclose integrated reports. Previous studies have observed that this voluntary corporate disclosure is a consequence of large firms' incentives associated with preventing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 111 publications
(135 reference statements)
1
31
0
4
Order By: Relevance
“…Recent literature on IR, which has been conducted within a voluntary setting, has rather focused on the determinants of IR disclosure (Frías‐Aceituno et al, ; García‐Sánchez, Martínez‐Ferrero, & Garcia‐Benau, ) and on the reduction of information asymmetry (Cuadrado‐Ballesteros et al, ; García‐Sánchez & Noguera‐Gámez, , ). Most of the literature regarding value relevance of IR has explored a mandatory setting in South Africa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent literature on IR, which has been conducted within a voluntary setting, has rather focused on the determinants of IR disclosure (Frías‐Aceituno et al, ; García‐Sánchez, Martínez‐Ferrero, & Garcia‐Benau, ) and on the reduction of information asymmetry (Cuadrado‐Ballesteros et al, ; García‐Sánchez & Noguera‐Gámez, , ). Most of the literature regarding value relevance of IR has explored a mandatory setting in South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers, such as García‐Sánchez and Noguera‐Gámez (), García‐Sánchez and Noguera‐Gámez (), and García‐Sánchez and Noguera‐Gámez (), examine the voluntary disclosure of IR. Their results indicate a reduction of information asymmetry and therefore a reduction of adverse selection costs when a firm discloses an IR.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Therefore, some researchers have extended the scope of these studies to integrated reporting. In this regard, some studies have analysed the impact of gender diversity (Alfiero, Cane, Doronzo, & Esposito, 2017;Fasan & Mio, 2017;Frias-Aceituno et al, 2013a;García-Sánchez & Noguera-Gámez, 2018;Gerwanski et al, 2019;Kilic & Kuzey, 2018), whereas others examined foreign diversity (Frias-Aceituno et al, 2013a) and age diversity (Alfiero et al, 2017). In relation to gender diversity, Frias-Aceituno et al (2013a) found that the presence of women on the board favours the adoption of integrated reporting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…add that companies located in countries with comply or explain integrated reporting regulation are more likely to adopt this practice Lueg, Lueg, Andersen, and Dancianu (2016),. through a case study of a Danish company, highlight how external pressures determined by the requests of shareholders, employees, local authorities, and customers are determining factors in the choice to adopt integrated reporting García-Sánchez and Noguera-Gámez (2018). underscore that firm incentives are the main determinants of integrated reporting and observe that there is a substitutive role between institutional country pressures and firm transparency decisions.…”
mentioning
confidence: 92%